(Retracted) An Evaluation of Public Policy Failure and Corruption in Nigeria: A Study of Niger Delta Development Commission (NDDC) - Oghuvbu, Ejiroghene Augustine (Journal of Governance, 2025)
This article has been retracted due to double publication in another journal. Based on the clarification from the author.One of the conditions of submission of a paper for publication in this journal is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. Re-use of any data should be appropriately cited. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal.